"Poplars and Cypresses” – that is the phenomenon of popularity of Populus Italica in the Kingdom of Poland in the 19th century - Boguszewska, Kamila Lucyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
Lombardy poplar is a tree with a distinctive cypress shape, which grows very fast and has little soil requirements. The species probably originated at the turn of the 17th and 18th century in Lombardy, where it spread via France and Germany, arriving at the territory of the Crown in the second half of the 18th century. However, it was only in the 19th century that its popularity reached its peak. The Lombardy poplar was being planted as a popular avenue plant. It was also an important part of the park complexes designed in a sentimental landscape style inspired by the work of Jean Jacques Rousseau. The article analyses the phenomenon of the popularity of poplar trees on the territory of the Kingdom of Poland in the context of the then literary and philosophical programme of the garden, whose two key sources are to be found in Arcadian literature – J. Milton's Paradise Lost, J. J. Rousseau's works such as New Heloise or Jacques Dellille's Gardens.